Role of Social Entrepreneurship Orientation in Environmental Turbulence to Agricultural Social Enterprise Performance in Indonesia - Wahyudi, Ach Firman; Kiminami, Akira; Yagi, Hironori (AGRARIS: Journal of Agribusiness and Rural Development Research, 2025)
Social entrepreneurship plays a critical role in addressing social challenges through innovative approaches, especially under environmental turbulence. This study investigated how Social Entrepreneurship Orientation (SEO) influences the financial and social performance of agricultural social enterprises in Indonesia, considering the moderating effect of environmental turbulence. Using purposive sampling, data were collected via an online survey from 106 agricultural social enterprise managers or owners across various Indonesian regions between February and July 2023. Structural Equation Modeling (SEM) was employed for analysis. Results denoted that SEO positively impacted both financial and social performance during environmental turbulence. Although environmental turbulence escalated SEO, it did not directly affect enterprise performance. Additionally, SEO mediated the relationship between environmental turbulence and financial and social performance, mitigating the turbulence’s adverse effect. These findings have highlighted SEO as a key capability for agricultural social enterprises to navigate dynamic environments and enhance their overall performance.